2023
DOI: 10.3390/d15030321
|View full text |Cite
|
Sign up to set email alerts
|

Cetaceans in the Mediterranean Sea: Encounter Rate, Dominant Species, and Diversity Hotspots

Abstract: We investigated the presence and diversity of cetaceans in the Mediterranean Sea, analysing the data collected by 32 different research units, over a period of 15 years (2004–2018), and shared on the common web-GIS platform named Intercet. We used the encounter rate, the species prevalence, and the Shannon diversity index as parameters for data analysis. The results show that cetacean diversity, in the context of the Mediterranean basin, is generally quite low when compared with the eastern Atlantic, as few sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
5
1
Order By: Relevance
“…Preliminary results based on visual surveys carried out in 2011-2013 have speculated this area as a favorable habitat for the Cuvier’s beaked whale (e.g. Bittau and Manconi, 2016; Gnone et al, 2023), and the results presented here, with data collected in recent year and with a continuous monitoring, can only support this hypothesis. In addition, the control stations used in this study (Figure 3) confirmed this result as well: the Cuvier’s beaked whale was detected only in stations B and C, which are located in proximity to the Canyon, but not in station A, located approximately 12 km north of it.…”
Section: Discussioncontrasting
confidence: 46%
See 3 more Smart Citations
“…Preliminary results based on visual surveys carried out in 2011-2013 have speculated this area as a favorable habitat for the Cuvier’s beaked whale (e.g. Bittau and Manconi, 2016; Gnone et al, 2023), and the results presented here, with data collected in recent year and with a continuous monitoring, can only support this hypothesis. In addition, the control stations used in this study (Figure 3) confirmed this result as well: the Cuvier’s beaked whale was detected only in stations B and C, which are located in proximity to the Canyon, but not in station A, located approximately 12 km north of it.…”
Section: Discussioncontrasting
confidence: 46%
“…Although DNA metabarcoding is more useful and cost-efficient when detecting greatest numbers of species at the same time (Gargan et al, 2022), cryptic species needs highly specific and sensitive approaches to be identified (Vörös et al, 2017). Compared to other cetaceans, the Cuvier’s beaked whale is one of the most difficult to study: these animals are able to dive at depth greater than 1 km (Schorr et al, 2014; Gnone et al, 2023) and for extended time period (1 hour, or more), and they also spend short periods at the surface (typically between 2 and 8 minutes) (Baird et al, 2006; Tyack et al, 2006; see also Figure 1). These traits make standard monitoring methods reasonably ineffective since for cetaceans that spend much of their life submerged, abundance estimates based on visual surveys become challenging and prone to underestimates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, both home and core ranges encompass critical habitats for fin whales in the North-Western Mediterranean Sea and agree well with prior knowledge on the presence and behaviour of fin whales in this portion of the Basin. Recent summer wide-scale aerial surveys [78][79][80], as well as studies based on photographic mark recapture [40,81] and visual [82] and acoustic surveys [27,83], 0q 3q E 6 q E 9 q E 1 2 q E 0 q 3q E 6 q E 9 q E 1 2 q E 0q 3q E 0 preferred habitat (% of daily occurrence) (for frequency estimate >1% of total days) 20 40 60 80 100 show a consistent seasonal use of the Balearic Sea, the slope, and offshore waters of the Gulf of Lion and the Corso-Provençal-Ligurian Basin for feeding purposes. In this context, our study demonstrates that animal-borne tracking technology can be used to support and consolidate other approaches.…”
Section: Home Range Estimation and Potential Feeding Habitatsmentioning
confidence: 99%